A genetic study of wild populations and evolution (1944)
The determination of the scientific basis of heredity within the last two decades and the verification of the principal conclusions in many different plants and animals has made possible the application of analytical methods in the study of variations in wild populations. As with the physical and chemical sciences, genetics has been enabled to make use of mathematics to compound (often theoretically) out of simple units, the genes, the complexity known as an organism, much in the same way as a chemist compounds molecules with atoms and the physicist compounds atoms with protons and electrons.